2022
DOI: 10.3390/antiox11020252
|View full text |Cite
|
Sign up to set email alerts
|

Ellagic Acid Alleviates Oxidative Stress by Mediating Nrf2 Signaling Pathways and Protects against Paraquat-Induced Intestinal Injury in Piglets

Abstract: The gastrointestinal tract is a key source of superoxide so as to be one of the most vulnerable to oxidative stress damage. Ellagic acid (EA), a polyphenol displays widely biological activities owing to its strong antioxidant properties. Here, we investigated the protective benefits of EA on oxidative stress and intestinal barrier injury in paraquet (PQ)-challenged piglets. A total of 40 weaned piglets were randomly divided into five groups: Control, PQ, 0.005% EA-PQ, 0.01% EA-PQ, and 0.02% EA-PQ. Piglets were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 70 publications
3
25
0
Order By: Relevance
“…In this study, oxidative stress induced by diquat stimulation significantly changed the morphological structure of intestinal villi, and decreased the activity of disaccharidase, protein content, RNA/DNA, and protein/DNA in piglets. Consistent with our research, Xiao et al showed that oxidative stress can lead to impaired intestinal barrier function in piglets [ 31 ]. Xu et al showed that oxidative stress can cause intestinal injury in piglets and significantly reduce the activity of intestinal digestive enzymes [ 32 ].…”
Section: Discussionsupporting
confidence: 92%
“…In this study, oxidative stress induced by diquat stimulation significantly changed the morphological structure of intestinal villi, and decreased the activity of disaccharidase, protein content, RNA/DNA, and protein/DNA in piglets. Consistent with our research, Xiao et al showed that oxidative stress can lead to impaired intestinal barrier function in piglets [ 31 ]. Xu et al showed that oxidative stress can cause intestinal injury in piglets and significantly reduce the activity of intestinal digestive enzymes [ 32 ].…”
Section: Discussionsupporting
confidence: 92%
“…Among them, ellagic acid (EA), a polyphenolic compound found in fruits, vegetables, and nuts, plays an important role against oxidative damage, inflammation, and Gram-positive pathogen infection [ 19 , 20 , 21 , 22 , 23 ]. Dietary EA was reported to effectively alleviate paraquat-induced liver oxidative damage [ 24 ] and intestinal damage [ 25 ] by regulating oxidative stress in post-weaning piglets. In addition, EA has strong antioxidant properties by scavenging ROS and increasing the antioxidant enzymes of the liver in D-galactose-challenged rats [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ellagic acid (EA) is a phenolic compound naturally present in many red fruits and berries. Apart from being the main product of ellagitannin hydrolysis, it is endowed with remarkable biological properties, including antioxidant [ 1 , 2 , 3 ], anti-inflammatory [ 4 ], antimicrobial [ 5 ], antidiabetic [ 6 ], antiviral [ 7 ], antidegenerative [ 8 ], and anticancer activities [ 9 ]. In addition to systemic uses, topical applications of EA have been widely described [ 10 ].…”
Section: Introductionmentioning
confidence: 99%